Students' Analogical Reasoning in Solving Geometry Problems Viewed from Visualizer's and Verbalizer's Cognitive Style - Shodikin, Ali; Murniasih, Tatik Retno; Faizah, Siti; Ekawati, Dea Wulan (Universitas Pendidikan Ganesha, 2023)
Many studies state that students' geometric problem-solving abilities in Indonesia are low. This research examines students' analogical reasoning in solving geometric problems in terms of their cognitive style. This descriptive qualitative research involves 32 class X high school students. The data collection methods used were tests, questionnaires, and interviews. The data analysis technique uses qualitative descriptive analysis. The results showed that the analogical reasoning of students with a visualizer cognitive style was superior to the analogical sense of students with a verbalizer cognitive style in solving geometric problems. Students with a visualizer cognitive style can achieve four components of analogical reasoning: encoding, inferring, mapping, and applying. Students with a verbalizer cognitive style only achieve two parts: encoding and inferring. The implication of this research is the need for educators to identify each student's learning style, which can be done through initial learning assessments and providing differentiated learning stimuli to students according to their cognitive style. Strengthening students with a verbalizer cognitive style needs to be emphasized more during the mapping and applying process, including providing appropriate scaffolding and allowing students to verbally express problem-solving strategies, teaching material by showing problem concept maps, and increasing practice on more varied questions.